Long term outcome of catastrophic antiphospholipid syndrome survivors. Issue 6 (1st June 2003) - Erkan, D; Asherson, R A; Espinosa, G; Cervera, R; Font, J; Piette, J-C; Lockshin, M D
Abstract : Background: Catastrophic antiphospholipid syndrome (APS) is defined as life threatening multiple organ thromboses developing simultaneously or over a short period. The survival rate of catastrophic APS is about 50%, but the long term outcome of patients who survive is unknown. Objective: To determine the long term outcome of patients with catastrophic APS and provide further information on patients who survived. Patients and methods: The clinical characteristics and outcomes of 130 patients with catastrophic APS have been reported previously. Six new cases were recently added to this series. Based on these publications, the authors who reported patients who had survived were contacted. Each author was asked ( a ) what treatment they gave their patients after the catastrophic APS; ( b ) if their patients had any further thrombosis. Results: 63/136 (46%) patients died at the initial event. Of the remaining 73 patients, information was available for 58 (79%). Thirty eight (66%) patients did not develop further APS related events during an average follow up of 67.2 months. Eleven (19%) patients developed further APS related events but were still alive. No patients developed further catastrophic APS. Nine (16%) patients died: due to multiple organ failure (three patients); myelofibrosis (one); pneumonia (one); and APS related events (four). Conclusion: Sixty six per cent of patients who survive an initial catastrophic APS event remained symptom free with anticoagulation during an average follow up of 67.2 months. Twenty six per cent of the survivors developed further APS related events and the mortality rate of these patients was about 25%.